The The Effect of Financial Ratios on Financial Distress Before and After the Covid-19 Pandemic in the Retail Subsector - Fatimah, Aila; Sutanti, Sutanti (Equity: Jurnal Ekonomi, 2025)
The purpose of this study is to analyze the effect of liquidity ratio, leverage and profitability on financial distress before and after the Covid-19 pandemic, as well as to analyze the difference in liquidity, leverage and profitability on financial distress before and after Covid-19. This study uses data from retail companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2023 period, where 2016-2019 is the pre-pandemic period and 2020-2023 is the post-pandemic period. Financial distress is measured using the springate method (s-score), for liquidity using the current ratio, leverage using the debt to equity ratio and profitability using return on assets. The results of the study show that liquidity has a significant effect on financial distress before the Covid-19 pandemic, but does not have a significant effect on financial distress after the Covid-19 pandemic. Leverage did not have a significant effect on financial distress before and after the Covid-19 pandemic. Profitability has a significant effect on the financial distress before and after the Covid-19 pandemic in the retail subsector listed on the IDX. Liquidity, leverage, and profitability simultaneously had a significant effect on financial distress before and after the Covid-19 pandemic in the retail subsector listed on the IDX. There was a significant difference between leverage against financial distress before and after the Covid-19 pandemic, but there was no significant difference between liquidity and profitability against financial distress before and after the Covid-19 pandemic in the retail subsector listed on the IDX.